Attenuated IL-2R signaling in CD4 memory T cells of T1D subjects is intrinsic and dependent on activation state - Schwedhelm, Katharine; Thorpe, Jerill; Murray, Sara A.; Gavin, Marc; Speake, Cate; Greenbaum, Carla; Cerosaletti, Karen; Buckner, Jane; Long, S. Alice (Clinical immunology (Orlando, Fla.), 2017)
The IL-2/IL-2R pathway is implicated in type 1 diabetes (T1D). While its role in regulatory T cell (Treg) biology is well characterized, mechanisms that influence IL-2 responses in effector T cells (Teff) are less well understood. We compared IL-2 responses in 95 healthy control and 98 T1D subjects. In T1D, low IL-2 responsiveness was most pronounced in memory Teff. Unlike Treg, CD25 expression did not influence the Teff responses. Reduced IL-2 responses in memory Teff were not rescued by resting, remained lower after activation and proliferation, and were absent in type 2 diabetes. Comparing basal IL-2 responses in resting versus activated cells, memory Teff displayed lower, but more sustained, responses to IL-2 overtime. These results suggest that T1D-associated defects in the Teff compartment are due to intrinsic factors related to activation. Evaluation of both Teff and Treg IL-2R signaling defects in T1D subjects may inform selection of therapies. •Low response to IL-2 is most prominent in memory CD4 Teff of T1D subjects.•Multiple factors influence T1D-associated low IL-2 response in Teff.•Low, but sustained TCR activation correlates with low basal IL-2R signaling.•Activation enhances low IL-2 responsiveness suggesting a regulated response.